2022
DOI: 10.3390/ijms23179742
|View full text |Cite
|
Sign up to set email alerts
|

Rhodococcus equi-Derived Extracellular Vesicles Promoting Inflammatory Response in Macrophage through TLR2-NF-κB/MAPK Pathways

Abstract: Rhodococcus equi (R. equi) is a Gram-positive coccobacillus that causes pneumonia in foals of less than 3 months, which have the ability of replication in macrophages. The ability of R. equi persist in macrophages is dependent on the virulence plasmid pVAPA. Gram-positive extracellular vesicles (EVs) carry a variety of virulence factors and play an important role in pathogenic infection. There are few studies on R. equi-derived EVs (R. equi-EVs), and little knowledge regarding the mechanisms of how R. equi-EVs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Nevertheless, Yang et al ( 31 ) reported that TSG-6 from bone marrow mesenchymal stem cells can protect against intervertebral disc degeneration via the TLR2/NF-κB signaling pathway. Moreover, TLR2 takes part in the inflammation response by activating the STAT3 and MAPK pathways ( 32 , 33 ). Additionally, Wu et al ( 34 ) showed that resveratrol blocks the IL-6/JAK/STAT3 pathway to protect HNPCs from degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Yang et al ( 31 ) reported that TSG-6 from bone marrow mesenchymal stem cells can protect against intervertebral disc degeneration via the TLR2/NF-κB signaling pathway. Moreover, TLR2 takes part in the inflammation response by activating the STAT3 and MAPK pathways ( 32 , 33 ). Additionally, Wu et al ( 34 ) showed that resveratrol blocks the IL-6/JAK/STAT3 pathway to protect HNPCs from degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis (ATCC 29212 strain) was cultured in brain heart infusion broth at 37°C overnight under anaerobic conditions to the stationary phase. The isolation of E. faecalis EVs was conducted as previously described with some modifications (Xu et al 2022). For identification of the isolated EVs, transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA) were performed to identify the isolated E. faecalis EVs.…”
Section: Methodsmentioning
confidence: 99%
“…Many bacteria, including R. equi and M. tuberculosis, produce extra-cellular vesicles (EVs) of approximately 20-500 nm in diameter, that play an important role in pathogenesis and host-pathogen interaction [40][41][42]. R. equi encodes homologues of the dynamin-like proteins IniA (REQ_40370; 50% identity, 67% similarity) and IniC (REQ_40360; 55% identity, 67% similarity), which are required for EV synthesis in M. tuberculosis [43].…”
Section: Plos Onementioning
confidence: 99%
“…Proteomic analysis M. tuberculosis EVs revealed the presence of 287 cell surface, secreted and some cytoplasmic proteins [47]. R. equi EVs contain trypsin-susceptible VapA, strongly suggesting that VapA is located on the surface of these vesicles [42]. Based on this study we propose the hypothesis that cell surface localisation of VapA is at least in part mediated by its disordered N-terminal domain and serves to facilitate high local VapA concentrations and, in addition, faciliates incorporation in EVs that may play a role in R. equi pathogenesis.…”
Section: Plos Onementioning
confidence: 99%